Nutritional Status Among Elderly in Ambulatory Care Setting - Karina Nurizky; Putri Teesa Radhiyanti Santoso; Muhammad Apriandi (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Nutritional status is a final outcome from a balance between food intake and body’s needs of the nutrients. Elderly is people whose age more than 60 years old. In Indonesia, elderly population has increased. Its phenomena is also known as population aging. Population aging is related to malnutrition in elderly. Malnutrition is defined as the insufficient, excessive or imbalanced consumption of nutrients.The objective of this study was to describe the nutritional status among elderly outpatients in geriatrics clinic of Dr. Hasan Sadikin General Hospital Bandung.Methods: This study was a descriptive cross-sectional study that used primary data in geriatrics clinic Dr. Hasan Sadikin General Hospital Bandung from September 2013 to October 2013. The sampling method was convenience sampling. This study was done with 43 elderly ( women, n=27 and men, n=16) outpatients.The nutritional status was classified by the questionnaire of Mini Nutritional Assessment into malnourished, risk of malnutrition and without malnutrition (adequate). After collecting the data, it was analyzed by Microsoft Excel in presenting the proportion of the elderly nutritional status.Results: Among all the respondents, 27 (63%) respondents had adequate nutrition and 16 (37%) respondents had risk of malnutrition. There was no respondent who had malnutrition (undernutrition). Conclusions: Majority of elderly outpatients in geriatrics clinic Dr. Hasan Sadikin General Hospital had adequate nutrition. DOI: 10.15850/amj.v4n2.1087